МОНГОЛЫН УЛС ТӨРИЙН СОЁЛ: ЁС ЗҮЙН ХЭМЖЭЭС - Ё.Довчин (Politology, 2023)
The author reviews empirical and theoretical works on the role political culture in politics. It seeks to clarify some specific features of mongolian political culture and explores the ways in which the descriptions of power relationships in accordance with poltical culture, especially ethical and value-based aspects. The text discusses political behaviour of elite in the democratic transitional period and is concerned particularly with the majority principles of democracy and the notion of popular rule. It attempts to describe some causal factors concerning with the decline of confidence in political institutions and political cynism. The author points out that political culture is main axis of modern political legitimacy shedding light on largely hidden aspects of the challences to democratic political process.